+0  
 
0
126
2
avatar

9(y-4)=-10(y+2 1 over 3)

Guest Mar 6, 2017
 #1
avatar
0

9 (y - 4) = -10 (y + 7/3)

 

9y - 36 = -10y - 70/3

9y + 10y = - 70/3 + 36

19y = 12 2/3

19y = 38/3

57y = 38

y = 38/57

y = 2/3 

Guest Mar 6, 2017
 #2
avatar+87309 
0

I assume this is :

 

9(y-4) = -10(y + 2 + 1 / 3)    simplify

 

9y - 36  = -10(y + 7/3)

 

9y - 36  = -10y - 70/3      add 10y, 36 to both sides

 

19y = 36 - 70/3

 

19y  =  108/3 - 70/3

 

19y = 38/3     divide both sides by 19

 

y = 2/3

 

 

cool cool cool

CPhill  Mar 6, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.